1-Aminocyclopropane-1-carboxylic acid induces resource reallocation in Pyropia yezoensis sporophytes - Uji, Toshiki; Sasaki, Shun; Mizuta, Hiroyuki (Frontiers in Plant Science, 2025)
Although the role of phytohormones in higher plants is well established, their role in macroalgae remains poorly understood. 1-Aminocyclopropane-1-carboxylic acid (ACC) is the immediate precursor of the plant hormone ethylene. However, recent studies suggested that ACC also acts as a signaling molecule to regulate growth and development independently of ethylene biosynthesis in land plants and red algae. This study investigated the role of ACC in the sporophytes of the red alga Pyropia yezoensis.ACC treatment significantly inhibited the growth of P. yezoensis sporophytes, whereas ethephon, an ethylene-releasing compound, had no such effect. In addition, ACC treatment promoted the degradation of photosynthetic pigments, including chlorophyll, phycobiliprotein, and carotenoids. The investigation employed RNA sequencing to identify differentially expressed genes in response to ACC treatment in sporophytes. Notably, upregulated genes such as proteases were associated with catabolic processes. By contrast, genes related to anabolic processes such as photosynthesis, including light-harvesting complex protein and Calvin–Benson cycle enzymes, were downregulated in response to ACC treatment. ACC induced catabolic processes and repressed anabolic processes, indicating the promotion of resource reallocation in microscopic sporophytes.